Answer:
(1)
Step-by-step explanation:
We will try:
(1) y =
x => 2 = 2 (seems legit)
(2) y = 4x => 2 = 32 (nope)
(3) y = x - 6 => 2 = 2 (yes but actually no because it is proportional relationship)
(4) y =
x - 2 => 2 = 2 (like the above)
Answer:
a=(-3.2)
Step-by-step explanation:
a+(-1.3)=(-4.5)=a-1.3=(-4.5)
a=(-3.2)
Please mark as Brainliest! :)
Have a nice day.
Hello from MrBillDoesMath!
Answer:
40
Discussion:
A diagram is always appreciated!
Assuming that
mAOC = mAOB + mBOC =>
108 = (3x + 4) + (8x - 28) => combine common terms
108 = (3x + 8x) + (4 - 28 ) =>
108 = 11x - 24 => add 24 to both sides
132 = 11x =>
x = 132/11 = 12
So mAOB = 3x + 4 = 3(12) + 4 = 36 + 4 = 40
Thank you,
MrB
Answer:
y/3. 1/3y
Step-by-step explanation:
1/3y is y/3 because 1*y=y